2020
DOI: 10.1371/journal.pone.0235513
|View full text |Cite
|
Sign up to set email alerts
|

Health system actors’ perspectives of prescribing practices in public health facilities in Eswatini: A Qualitative Study

Abstract: Background Rational medicines use (RMU) is the prescribing/dispensing of good quality medicines to meet individual patient's clinical needs. Policy-makers, managers and frontline providers play critical roles in safeguarding medicine usage thus ensuring their rational use. This study investigated perspectives of key health system actors on prescribing practices and factors influencing these in Eswatini. Public sector healthcare service delivery is through health facilities (public sector, not-for-profit faith-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Since then, the final draft of the Kingdom of Eswatini NAP to curb AMR was made available at the end of 2017, with the Government fully committed to curbing the spread of AMR in the country [8]. This is needed given the findings in ambulatory care in 2015 [18], from a study undertaken in Piggs Peak Government Hospital between 2014 and 2015 showing that the physicians in the hospital prescribed a range of antibiotics to treat patients with community acquired pneumonia with limited following of current national guidelines [19].Ncube et al (2020) identified a general need to improve the prescribing of medicines in the Kingdom given the extent of inappropriate prescribing [20].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the final draft of the Kingdom of Eswatini NAP to curb AMR was made available at the end of 2017, with the Government fully committed to curbing the spread of AMR in the country [8]. This is needed given the findings in ambulatory care in 2015 [18], from a study undertaken in Piggs Peak Government Hospital between 2014 and 2015 showing that the physicians in the hospital prescribed a range of antibiotics to treat patients with community acquired pneumonia with limited following of current national guidelines [19].Ncube et al (2020) identified a general need to improve the prescribing of medicines in the Kingdom given the extent of inappropriate prescribing [20].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently prescribed drugs, including antibiotics for treating malaria, can be attributed to various factors but are not limited to the lack of knowledge of the prescriber, false belief, peer influence, and misunderstanding of normal findings of malaria (i.e., most of the prescribers relate malaria symptoms with typhoid fever due to similar symptoms) [38,39,40]. Irrational prescribing trends can also be attributed to limited pharmacists' role in healthcare facilities, which is regarded more as managing and dispensing drugs rather than advising in clinical prescribing for managing diseases [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The World Bank has also defined RUM in two tiers: (i) the utilization of medicines based on scientific data regarding drug efficacy, safety, and compliance; and (ii) the need to maximize the benefit of medicine in the resource-limited health system to ensure cost-efficacy ( 232 , 233 ). RUM has been considered as the strategic issue in providing effective and quality healthcare ( 234 , 235 ).…”
Section: Rational Use Of Medicine and Irrational Prescribing Of Antimmentioning
confidence: 99%